Structural evolution of toll-like receptor 7/8 agonists from imidazoquinolines to imidazoles. Issue 7 (14th May 2021) - Kaushik, Deepender; Kaur, Arshpreet; Petrovsky, Nikolai; Salunke, Deepak B.
Abstract : TLR7/8 agonists are emerging as promising vaccine adjuvant candidates. An evolution of imidazole based TLR7/8 agonist from imidazoquinoline based scaffold is delineated along with the elaboration of detailed structure activity relationship (SAR) in each chemotype. Abstract : Several synthetic heterocyclic small molecules like imiquimod, resiquimod, CL097, CL075, bromopirone, tilorone, loxoribine and isatoribine demonstrated TLR7/8 agonistic activity and relatively modest structural changes in such molecules result in major variation in the TLR7 and/or TLR8 activity. A strict dependency of the electronic configuration of the heterocyclic system was also observed to influence the agonistic activity. In the present review, an evolution of imidazole based TLR7/8 agonist from imidazoquinoline based scaffold is delineated along with the elaboration of detailed structure activity relationship (SAR) in each chemotype. The structural and activity details of not only the active compounds but also the related inactive compounds are included to better understand the SAR. TLR7/8 agonists are emerging as promising vaccine adjuvant candidates and the present SAR and structural information will provide a road map towards the identification of more potent and appropriate candidates for further drug discovery.